Bluebeard's eighth wife = Blaubarts achte Frau - Brackett, Charles 1892-1969; Wilder, Billy 1906-2002; Savoir, Alfred 1883-1934 (Universal Studios, 2011)
"US multi-millionaire Michael Barndon marries his eighth wife, Nicole, the daughter of a broken French Marquis. But she doesn't want to be only a number in the row of his ex-wives and starts her own strategy to 'tame' him.
Spielfilm, Orig.: USA, 1938
Keywords: Filmkomödie; Liebesfilm; Verfilmung; Savoir, Alfred / 1883-1934 / Film adaptations; Man-woman relationships / France / Riviera / Drama; Married people / Drama; Prenuptial agreements / Drama; Millionaires / United States / Drama; Divorced men / Drama; Riviera (France) / Drama; Feature films; Savoir, Alfred / 1883-1934; Divorced men; Man-woman relationships; Married people; Millionaires; Prenuptial agreements; France / Riviera; United States; Feature films / United States; Drama; Fiction films; Film adaptations; Romantic comedy films; Comédies romantiques (Films); Films de fiction; Film; DVD-Video